FINE NEEDLE ASPIRATION CYTOLOGY OF SALIVARY GLAND LESIONS WITH CATEGORIZATION BASED ON MILAN SYSTEM – A 5-YEAR RETROSPECTIVE STUDY - SINGAL, POONAM; GARG, MONIKA; KAUR, AMRINDER; BANSAL, SUKRITI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Fine needle aspiration cytology (FNAC) is a well-established technique for initial assessment of salivary gland lesions. The Milan system for reporting salivary gland cytopathology (MSRSGC) was introduced to provide a guide for diagnosis and management of salivary gland lesions according to risk of malignancy (ROM) in different categories. Methods: A 5-year retrospective study was conducted to reclassify the salivary gland lesions from previous diagnosis. Clinical data, FNAC, and histopathology report was retrieved and cases were reclassified according to the Milan system of classification. Risk of malignancy was calculated for each category. The positive predictive value, negative predictive value, and diagnostic accuracy of FNAC was calculated. Results: A total of 314 cases were evaluated cytologically. Histopathology was available in 81 cases. The distribution of cases in different categories according to the Milan system was 1.27% (Cat I), 48.4% (Cat II), 1.91% (Cat III), 38.21%, (Cat IV A), 2.22% (Cat IV B), 3.18% (Cat V), and 4.77% (Cat VI). Overall risk of malignancy reported was 0%, 0%, 50%, 14.7% (Cat IV A), 66.66% (Cat IV B), 83.3%, and 100%, respectively. Overall sensitivity, specificity, positive predictive value, and negative predictive value was 70.58%, 93.75%, 75%, and 92.30%, respectively. Diagnostic accuracy was 88.89%. Conclusion: MSRSGC is a useful system for conveying risk of malignancy (ROM) and deciding further treatment protocol and, hence, improves overall patient care and management.